A evasão dos cursos de licenciatura em geografia da Universidade Estadual do Oeste Do Paraná (Unioeste) - Wilhelm, Marilene Francieli (2019)
School dropout in higher education is a topic that presents several questions and complexity. Based on this problem, the need to expand and deepen the study on university school dropout resumes this research. It was chosen as a research focus, to understand the issue of evasion in the Geography Degree Courses, in the specific case of the Geography Courses offered by the State University of the West of Paraná (UNIOESTE), Campus of Marechal Cândido Rondon / PR and Campus Francisco Beltrão / PR The temporal focus was limited to the years 2010 to 2016, in order to examine the indices and perform analysis between the years cited to define the profile of the evaded students and to reveal the reasons that influence the occurrence of evasion. The research, which is predominantly qualitative, in addition to being bibliographical, takes the form of a case study, with the participation of students who have been evaded from the Geography Undergraduate Courses, through a semistructured interview / questionnaire. It began with the consultation of official national and state documents on registrations and evasions, including, in this search for information, books, articles, theses, dissertations on the subject. With the data thus obtained, tables and graphs were elaborated, figures which, together with the bibliographical survey, provided data whose analysis allowed a realistic view of university school dropout in the aforementioned undergraduate courses and allowed to identify factors that could decrease the evasion.